Appraisal of universal health insurance and maternal health services utilization: pre- and post-context of the Jaminan Kesehatan Nasional implementation in Indonesia - Rahmawati, Tati; Hsieh, Hui-Min (Frontiers in Public Health, 2024)
Introduction: The Indonesian government introduced universal health insurance through the National Social Security System (JKN) in 2014 to enhance overall healthcare. This study compares maternal health care (MHC) service utilization before and after JKN implementation in Indonesia. Method. Using 2012 and 2017 data from Indonesia Demographic and Health Surveys (DHS), we conducted a two-period cross-sectional design study following the Anderson model. We assessed how the JKN policy and population characteristics influenced healthcare utilization for women aged 15-49 who had given birth in the last five years. Multivariable logistic regression models were used to assess the impact of the JKN policy and related factors. Result. In two waves of Indonesia DHS with 14,782 and 15,021 subjects, this study observed a significant increase in maternal healthcare service utilization post-JKN implementation. Women were more likely to have at least four antenatal care visits (adjusted odds ratio, AOR=1.17), receive skilled antenatal care (AOR=1.49), obtain skilled birth assistance (AOR=1.96), and access facility-based delivery (AOR=2.45) compared with pre-JKN implementation. Conclusion. This study revealed a significant positive impact of JKN on enhancing MHS utilization. The introduction of universal health insurance coverage likely reduced financial barriers for specific demographics, resulting in increased service utilization. Our study may offer valuable insights for Asian countries with similar demographics and health insurance implementations.